2008
DOI: 10.1002/hrm.20198
|View full text |Cite
|
Sign up to set email alerts
|

Strategic human resource management, firm performance, and employee relations climate in China

Abstract: We examined strategic human resource management (SHRM) and human resource practices in the People's Republic of China to assess the impact of these practices on firm performance and the employee relations climate. We also tested whether firm ownership moderates the above relationships. Empirical results from a sample of Chinese firms from various industries and regions showed that the levels of adoption of SHRM and HR practices were lower in state‐owned enterprises (SOEs) than in foreign‐invested enterprises (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
124
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 54 publications
2
124
0
3
Order By: Relevance
“…We consider this is significant given that different organisational ownerships' embedded institutional elements influence organisational strategies and practices, which might affect the type of stressors to which an individual is exposed, and in turn lead to different individual outcomes. Existing studies have demonstrated the moderating effect of ownership on the HRM-firm performance relationship in the Chinese context (Law et al, 2003;Ng & Siu, 2004;Ngo et al, 2008;Wei & Lau, 2008).Providing further support to the importance of ownership, we found that organisational ownership can significantly impact on the stress-job satisfaction relationship. This dimension requires consideration both as a potentially important variable in research on HR practices; it also needs to be disaggregated and its key components distinguished and analysed separately.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…We consider this is significant given that different organisational ownerships' embedded institutional elements influence organisational strategies and practices, which might affect the type of stressors to which an individual is exposed, and in turn lead to different individual outcomes. Existing studies have demonstrated the moderating effect of ownership on the HRM-firm performance relationship in the Chinese context (Law et al, 2003;Ng & Siu, 2004;Ngo et al, 2008;Wei & Lau, 2008).Providing further support to the importance of ownership, we found that organisational ownership can significantly impact on the stress-job satisfaction relationship. This dimension requires consideration both as a potentially important variable in research on HR practices; it also needs to be disaggregated and its key components distinguished and analysed separately.…”
supporting
confidence: 75%
“…We consider this is significant given that different organisational ownerships' embedded institutional elements influence organisational strategies and practices, which might affect the type of stressors to which an individual is exposed, and in turn lead to different individual outcomes. Existing studies have demonstrated the moderating effect of ownership on the HRM-firm performance relationship in the Chinese context (Law et al, 2003;Ng & Siu, 2004;Ngo et al, 2008;Wei & Lau, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such they suggest that further convergence in HRM practices between the west and China is likely over the coming years. However, other authors note that SOEs tend to face significant constraints in the implementation of results-8 based performance appraisal because of long-standing institutional factors, such as the conflicting policy pressures from local government, central government and trade unions (Ngo, Lau and Foley 2008). Moreover, the skills and experiences of managers in SOEs tend to be somewhat limited and initiating change can be difficult when many employees continue to identify with pre-reform norms and values (Warner, Goodall and Ding 1999;Ngo, Lau and Foley 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, other authors note that SOEs tend to face significant constraints in the implementation of results-8 based performance appraisal because of long-standing institutional factors, such as the conflicting policy pressures from local government, central government and trade unions (Ngo, Lau and Foley 2008). Moreover, the skills and experiences of managers in SOEs tend to be somewhat limited and initiating change can be difficult when many employees continue to identify with pre-reform norms and values (Warner, Goodall and Ding 1999;Ngo, Lau and Foley 2008). In comparison to SOEs, FIEs face fewer institutional constraints and have greater flexibility and autonomy in how they implement and manage their HRM systems, including performance appraisal (Chow, 1992;Warner, Goodall and Ding, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%